PERSEPSI SISWA TENTANG PRIBADI KONSELOR YANG DIHARAPKAN DI SMK PGRI WONOASRI KABUPATEN MADIUN TA 2014/2015 - Mudjijanti, Fransisca (Widya Warta, 2017)
The purpose of this study was to analyze the perception on ideal counselors’ personalities according to the students of SMK PGRI Madiun Wonoasri for the 2014/2015 academic year  and whether the counselor personalities were in conformity with the ideal expectation of the students. The research population were all students of SMK PGRI Wonoasri for the 2014/2015 academic year, namely 1000 students. Using cluster random sampling, the total samples of this research were set at 25% of the population, namely 250 students. The data collection tool was the perception scale developed into the form of positive and negative statements following the Likert scale model with four alternative answers. The data analysis technique was descriptive percentage method (DP). The conselors who had ideal personalities according to the students can be sorted based on the indicator variables;  the highest percentage obtained from the subjects marking ‘appropriate’ and ‘very appropriate’ in their resposes was 1) Warm and friendly (97.6%), 2) Competent (99.2%), 3) Patience (97.4%), 4) Trustworthy and honest (97.5%), 5) Dignified (90.8%), and 6) Consistent (78.7%). The counselors who did not have ideal personalities were the ones who were only friendly at school and who did not get sense of humour.